TRIBUTE: Remembering David Webster one year later - Vogelman, Lloyd (PINS-Psychology in Society, 2025)
At approximately 12.00 pm on May Day 1989, I heard the news that Dave Webster had been shot. Nearly an hour later his shooting was confirmed and I was also informed he was dead. "Impossible" was the only word that rang true to me. Dave Webster could not die. He was too much part of life. He was too much part of progressive Life in South Africa. He was too much part of mine, my friends and colleagues’ history. Dave had been around when we were in the student movement. He was one of the few academics we could consult. His dedication, loyalty, gentleness, knowledge and expertise ensured that we were at his door frequently. He listened for many hours of his life to our worries and plans. In time David became a role model for how we would like to be when we graduated. He probably never realised the influence and impact he had on us then and how he influenced a whole generation of students and student leaders.